Senam Hipertensi dan Pemeriksaan Tekanan Darah sebagai Upaya dalam Pencegahan dan Pengendalian Hipertensi pada Lansia - Restawan, I Gede; Mutmainnah, Mutmainnah; Purwiningsih, Sri; Susanto, Denny (Universitas Baiturrahim, 2024)
Hypertension is high blood pressure that is often found in the elderly population. Currently, the prevalence of hypertension in Sigi Regency is still quite high, namely 1,325 people. Meanwhile, there are still many hypertension sufferers who do not control their blood pressure. Thus, preventive and control measures are needed so that serious complications do not occur in sufferers. Actions that can be taken to achieve positive results for hypertension sufferers in controlling their blood pressure are by conducting direct blood pressure checks, health education and hypertension exercise training. The purpose of this community service is to increase public knowledge and awareness in controlling and controlling their blood pressure within normal limits. The method used is through lectures and direct training (demonstrations and simulations) on hypertension exercise. The results of this community service activity showed an increase in knowledge about hypertension and a decrease in average systolic and diastolic blood pressure. In addition, participants were able to do hypertension exercise movements correctly and independently after participating in the training. Counseling and training in hypertension exercise are very important because they provide significant benefits in increasing public knowledge in order to maintain optimal blood pressure and prevent more serious complications.